2002
DOI: 10.1080/003655902317259300
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Replantation of Sexual Organs in Three Patients

Abstract: Microsurgical reconstruction of penis and testes with the use of vessel grafts prolonged the hypoxia which led to necrosis. Disturbances in vein blood outflow from the sutured organs contributed to this process as well. The third case resulted in success mostly due to quick intervention (5 h from injury) as well as to proper microsurgical reconstruction of vessels, nerves, and urethra. In addition suprapubic urine diversion was successfully applied and the urethra healed on the perforated catheter. Routine ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Similar to limbs, the penis consists of skin, blood vessels, nerves, cavernous bodies, albuginea, and urethral mucosa, making penile transplantation a composite tissue transplantation [ 14 ], and the rejection reactions are usually more serious than in single organ transplantation [ 15 , 16 ]. Results from animal studies have shown that penis autotransplantations had a high success rate; however, allogeneic penis transplantation still remains a challenge for clinicians [ 17 , 18 ]. Penis defects do not endanger the life of the patients but cause profound psychological problems that greatly affect the patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to limbs, the penis consists of skin, blood vessels, nerves, cavernous bodies, albuginea, and urethral mucosa, making penile transplantation a composite tissue transplantation [ 14 ], and the rejection reactions are usually more serious than in single organ transplantation [ 15 , 16 ]. Results from animal studies have shown that penis autotransplantations had a high success rate; however, allogeneic penis transplantation still remains a challenge for clinicians [ 17 , 18 ]. Penis defects do not endanger the life of the patients but cause profound psychological problems that greatly affect the patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%